Determining the Stress Field in Active Volcanoes Using Focal Mechanisms - Massa, Bruno; D'Auria, Luca; Cristiano, Elena; De Matteo, Ada (Frontiers in Earth Science, 2016)
Stress inversion of seismological datasets became an essential tool to retrieve the stress field of active tectonics and volcanic areas. In particular, in volcanic areas, it is able to put constrains on volcano-tectonics and in general in a better understanding of the volcano dynamics. During the last decades, a wide range of stress inversion techniques has been proposed, some of them specifically conceived to manage seismological datasets. A modern technique of stress inversion, the BRTM, has been applied to seismological datasets available at three different regions of active volcanism: Mt. Somma-Vesuvius (197 Fault Plane Solutions, FPSs), Campi Flegrei (217 FPSs) and Long Valley Caldera (38,000 FPSs). The key role of stress inversion techniques in the analysis of the volcano dynamics has been critically discussed. A particular emphasis was devoted to performances of the BRTM applied to volcanic areas.